Integrating Space Syntax Analysis and Community Perceptions of Streetscape for Urban Conservation of Angono, Rizal - Intalan, Lawrence F. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2025)
Urban conservation is increasingly recognized as a vital aspect of sustainable development, preserving not only physical structures but also the cultural narratives that imbue spaces with significance. In the Philippines, the town of Angono in Rizal province is well-known for its rich cultural heritage, with a history deeply intertwined with its local arts, traditions, and community identity. Angono’s heritage district, where the old streets are situated, represents an invaluable resource for both local and national heritage. However, as urbanization encroaches on this area, it becomes imperative to adopt strategies that ensure its cultural landscapes are preserved for future generations. This research focuses on mapping the heritage district of Angono, Rizal, with the aim of advancing urban conservation. The study employs Space Syntax analysis and community perceptions of the urban streetscape as its primary methodologies. Space Syntax, a tool for analyzing spatial configurations, will provide insights into the changing patterns of movement, accessibility, and connectivity within Angono’s urban fabric. This method will help to identify how new developments are influencing the town’s spatial dynamics and streetscape character. Complementing this, an examination of community perceptions will offer a deeper understanding of how local residents experience and value these changes, providing a critical perspective on the impacts of urban transformation on social and cultural identity. The result of the study reveals a strong correlation between the most integrated and connected streets, as identified by Space Syntax analysis, as well as the streets and landmarks most recognized by the community. Additionally, the maps demonstrate that key landmarks are clustered at specific urban nodes within Angono's heritage district, where much of the cultural heritage is concentrated. These insights can guide local government units (LGUs) in recognizing the value of urban conservation integrated in infrastructure planning, serving as a crucial resource for shaping both immediate and long-term development strategies.